Ageing and quality of life in family carers of people with dementia being cared for at home: a literature review - de Oliveira, Deborah Cristina; Vass, Catherine D.; Aubeeluck, Aimee (Insight Medical Publishing Group, 2015)
Background: Despite the increasing older population providing care for family members with dementia at home, there is no consensus in the literature in terms of how caring impacts on their quality of life (QoL) and the association of the family carer's age with QoL outcomes. Aims: To explore the available literature investigating the QoL of older family carers (family carers aged > 60) and the association of family carers' age and QoL outcomes in a dementia context. Methods: A review of the literature to December 2013 was conducted using Embase-O VID, CINAL, Medline-OVID, Psyc INFO-OVID, Grey literature and the references of the included studies. Cross-sectional or prospective longitudinal studies published in English were eligible. The selection and appraisal processes were performed by two reviewers independently and the methodological quality was assessed by STROBE statement. Results: From the 12 selected studies, 4 were carried out with older family carers' samples and 8 associated the variable 'age' with QoL outcomes. Eight different instruments were used to assess family carers' QoL, however none were designed specifically for older people or older family carers. The mean age of the carers' samples ranged from 55.2 to 76.0 years old. Older family carers showed low levels of QoL and were often below the age-matched standard population. Carers' age was negatively correlated with QoL outcomes in most of the studies. Conclusion: Older people are increasingly involved with dementia care and family carer's advanced age was shown to be associated with low levels of QoL. Future research should investigate the QoL of older family carers separately and use QoL instruments containing older family carers' specific needs and perspectives of QoL. In planning care and support, primary health care practitioners should consider family carer's age group and their specific needs.